Erratum: Large meta-analysis of genome-wide association studies identifies five loci for lean body mass - M. Carola Zillikens; Serkalem Demissie; Yi-Hsiang Hsu; Laura M. Yerges-Armstrong; Wen-Chi Chou; Lisette Stolk; Gregory Livshits; Linda Broer; Toby Johnson; Daniel L. Koller; Zoltán Kutalik; Jian’an Luan; et al. (Nature Communications, 2017)
A correction to this article has been published and is linked from the HTML version of this article.